2011
DOI: 10.1111/j.1754-9485.2011.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiotherapy for T4 non-melanoma skin carcinoma

Abstract: Patients presenting with untreated lesions, smaller tumour volumes (<70 cm(3)) postoperatively, basal cell histology and absence of bone erosion or nodal disease have improved local control and outcomes. Basal cell carcinoma and SCC should be staged and treated as two separate disease entities. The use of IMRT for advanced skin cancer warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…18 We found five studies including 191 patients that reported deaths as a result of SCC, 547,585,[588][589][590] with an average of 9.1% of patients dying from their disease on pooled analysis (95% CI 1.4% to 22.8%; I 2 = 79%) 23,67,[70][71][72] ( Figure 43). The greatest proportion of deaths was observed in a study of advanced T4 tumours in which two of three patients with eligible SCCs died (66%, 95% CI 9.4% to 99.1%) 590 during a mean follow-up period of 14 months. For studies with mean duration of follow-up between 2 and 5 years, the average recurrence was 4.8% (119 patients, 95% CI 1.6% to 9.8%).…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 99%
See 4 more Smart Citations
“…18 We found five studies including 191 patients that reported deaths as a result of SCC, 547,585,[588][589][590] with an average of 9.1% of patients dying from their disease on pooled analysis (95% CI 1.4% to 22.8%; I 2 = 79%) 23,67,[70][71][72] ( Figure 43). The greatest proportion of deaths was observed in a study of advanced T4 tumours in which two of three patients with eligible SCCs died (66%, 95% CI 9.4% to 99.1%) 590 during a mean follow-up period of 14 months. For studies with mean duration of follow-up between 2 and 5 years, the average recurrence was 4.8% (119 patients, 95% CI 1.6% to 9.8%).…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 99%
“…However, the number of patients was very small (n = 5) and, in one of the studies, 590 only T4 tumours were treated with recurrence in two out of three patients. Average recurrence in the two studies with specified mean duration of follow-up of between 2 and 5 years was 6.1% (44 patients, 95% CI 0% to 22.6%).…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 99%
See 3 more Smart Citations